Police discretion in India - Mohanty, Satyajit, author.
1 online resource
Keywords: "This book is the first empirical study of police discretion in India. Going beyond anecdotal accounts, it addresses the issues and concerns of arrest discretion behaviour of police with analysis of available literature internationally, testing the validity in the context of police in India and explaining the gap that exists between the legislative intent and field law enforcement. It establishes how extralegal determinants like subculture, environment, and situations influence arrest discretion as much as legal determinants such as statutes, rules, manuals, and court rulings. It also provides vital explanations on the workings of the police system in India. The volume will be of great interest to policy makes, police leaders, officers of judiciary, scholars and researchers of criminology and criminal justice, sociology and social anthropology and South Asian studies"--